Cytogenetics in multiple myeloma patients progressing into extramedullary disease - Bešše, Lenka; Sedlaříková, Lenka; Grešliková, Henrieta; Kupská, Renata; Almasi, Martina; Penka, Miroslav; Jelínek, Tomáš; Pour, Luděk; Adam, Zdeněk; Kuglík, Petr; Krejčí, Marta; Hájek, Roman; et al. (European journal of haematology, 2016)
BACKGROUND: Extramedullary disease in multiple myeloma patients is an uncommon event occurring either at the time of diagnosis, or during disease progression/relapse. This manifestation is frequently associated with poor outcome and resistance to treatment. We evaluated chromosomal alterations of plasma cells of multiple myeloma patients with extramedullary relapse, either in the bone marrow (BM) or at extramedullary sites, and in previous BM collection by interphase fluorescence in situ hybridization. MATERIAL AND METHODS: Thirty-one patients [25 BM plasma cells (BMPCs), 18 extramedullary tumor plasma cells], of which 12 had paired samples of BM and extramedullary plasma cells and 14 had previous collection of BM, were investigated for the presence of chromosomal aberrations (CHAs): del(17)(p13), del(13)(q14), 14q32 disruption, t(4;14)(p16;q32), t(14;16)(q32;q23), gain(1)(q21), and hyperdiploidy status. RESULTS: Overall, in unrelated samples, t(4;14) was more prevalent in extramedullary plasma cells, and hyperdiploidy was more frequent in BMPCs. In paired samples, there was a higher frequency of del(13)(q14) and 14q32 disruption in BMPCs. Frequency of all studied CHAs was higher in BMPCs of extramedullary patients than in their previous sample collection. CONCLUSION: These data show that plasma cells harbor more aberrations during their transformation into extramedullary form.
Keywords: Female; lidé středního věku; kostní dřeň; translokace genetická; progrese nemoci; Bone Marrow; staging nádorů; mužské pohlaví; metastázy nádorů; Biomarkers, Tumor; senioři nad 80 let; Humans; dospělí; Chromosome Aberrations; nádorové biomarkery; Multiple Myeloma; lidé; Middle Aged; Neoplasm Staging; chromozomální aberace; Translocation, Genetic; Aged, 80 and over; senioři; Neoplasm Metastasis; hybridizace in situ fluorescenční; ženské pohlaví; mnohočetný myelom; In Situ Hybridization, Fluorescence; Disease Progression; Aged; Adult; Male